2019
DOI: 10.1002/ece3.5060
|View full text |Cite
|
Sign up to set email alerts
|

Urbanization and the temporal patterns of social networks and group foraging behaviors

Abstract: Urbanization causes dramatic and rapid changes to natural environments, which can lead the animals inhabiting these habitats to adjust their behavioral responses. For social animals, urbanized environments may alter group social dynamics through modification of the external environment (e.g., resource distribution). This might lead to changes in how individuals associate or engage in group behaviors, which could alter the stability and characteristics of social groups. However, the potential impacts of urban h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 60 publications
1
9
1
Order By: Relevance
“…The feeders were filled with black oil sunflower seeds and kept filled throughout the duration of the study. The feeders were located ∼130 m apart, a distance that made it likely that we were sampling the same chickadee population at both locations (Bartmess-LeVasseur et al, 2010; Book & Freeberg, 2015); black-capped chickadee flock size varies from three to 12 birds (Jones et al, 2017), and flocks are typically stable over the course of a winter (Jones et al, 2019; Krams et al, 2012). Based on the pairs/groups of birds that visited the feeders together, we estimated that at least four flocks were represented in the population sampled, and there was some evidence that flock composition fluctuated near the end of winter.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The feeders were filled with black oil sunflower seeds and kept filled throughout the duration of the study. The feeders were located ∼130 m apart, a distance that made it likely that we were sampling the same chickadee population at both locations (Bartmess-LeVasseur et al, 2010; Book & Freeberg, 2015); black-capped chickadee flock size varies from three to 12 birds (Jones et al, 2017), and flocks are typically stable over the course of a winter (Jones et al, 2019; Krams et al, 2012). Based on the pairs/groups of birds that visited the feeders together, we estimated that at least four flocks were represented in the population sampled, and there was some evidence that flock composition fluctuated near the end of winter.…”
Section: Methodsmentioning
confidence: 99%
“…However, winter flocks of great tits have been characterized as fusion-fission, with individual birds' associations varying over the course of the winter (Aplin et al, 2013). In contrast, black-capped chickadees form more stable winter associations (Jones et al, 2017(Jones et al, , 2019Krams et al, 2012), with small flocks consisting of three to 12 individuals (Jones et al, 2017), and linear dominance hierarchies (Devost et al, 2016). Personality of black-capped chickadees is not related to social dominance at feeders (Devost et al, 2016) or food neophobia (Prasher et al, 2019), and does not influence social transmission of information (Jones et al, 2017), but in these studies, personality was assessed by behavior in captivity (Prasher et al, 2019) or in an open-field cage trial following capture, which may not have been fully representative (Devost et al, 2016;Jones et al, 2017).…”
mentioning
confidence: 99%
“…Detailed spatial information about species presence often aids in the definition of new or distinct populations as well as the understanding of habitat use and movement patterns (e.g., Baird et al, 2010; Scofield et al, 2011; Sequeira et al, 2018). Continuous temporal data facilitate description of key patterns in animal activity, which is crucial for understanding foraging strategies and mitigating harmful anthropogenic interactions (Forney et al, 2011; Jones et al, 2019; Soldevilla et al, 2011). Characterization of spatiotemporal patterns in odontocete (toothed whale) species presence may also facilitate the creation and comparison of habitat models (e.g., Kanaji et al, 2017; Seger & Miksis‐Olds, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last two decades, research across a range of taxa has confirmed that individual social network position has fitness consequences [8][9][10][11][12][13][14][15][16][17][18][19][20]. Position within a network is known to be a repeatable trait both within the same group [21][22][23][24][25] and in some species across social contexts [26][27][28]. Revealing the sources of variation in individual network position has led to a deeper understanding of how and when such traits are expected to evolve [29,30].…”
Section: Introductionmentioning
confidence: 99%